Fintech Lending: An Analysis of Supply Factors in Indian Context - Maity, Sagnik; Majumder, Amit (Management Journal for Advanced Research, 2023)
With a risen technological advancement, the lending sector has changed the way it serves borrowers. Fintech lenders are those who depend on this type of advancement and create a positive effect on the lending sector in India. The primary goal of this research paper is to comprehend the supply drivers of fintech lending in India. To fulfil this goal, researchers create a conceptual framework based on secondary sources of information. In conclusion, there are four drivers that make the supply line stable for the fintech lenders in India. The results of this study can be used to refine a case study approach for use in other studies.